2011
DOI: 10.1590/s1678-91992011000100011
|View full text |Cite
|
Sign up to set email alerts
|

Neutralization of pharmacological and toxic activities of Bothrops jararacussu snake venom and isolated myotoxins by Serjania erecta methanolic extract and its fractions

Abstract: Most of the snakebites recorded in Brazil are caused by the Bothrops genus. Given that the local tissue damage caused by this genus cannot be treated by antivenom therapy, numerous studies are focusing on supplementary alternatives, such as the use of medicinal plants. Serjania erecta has already demonstrated anti-inflammatory, antiseptic and healing properties. In the current study, the aerial parts of S. erecta were extracted with methanol, then submitted to chromatographic fractionation on a Sephadex LH20 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Reactive oxygen species are involved in the pathogenesis of gastric lesions, , and antioxidants play an important role in protecting against such damage. It has been shown that rutin at a dose of 200 mg kg –1 showed a gastroprotective effect against 50% ethanol-induced ulcers, and this effect may be related to the antioxidant properties, since rutin was able to decrease the levels of lipoperoxide and increase the antioxidant activity of the enzyme GSH-Px .…”
Section: Results and Discussionmentioning
confidence: 99%
“…Reactive oxygen species are involved in the pathogenesis of gastric lesions, , and antioxidants play an important role in protecting against such damage. It has been shown that rutin at a dose of 200 mg kg –1 showed a gastroprotective effect against 50% ethanol-induced ulcers, and this effect may be related to the antioxidant properties, since rutin was able to decrease the levels of lipoperoxide and increase the antioxidant activity of the enzyme GSH-Px .…”
Section: Results and Discussionmentioning
confidence: 99%
“… 24 Its is alreay proved that the methanolic extract and fractions of Serjania erecta rich in flavonoids and tannins exhibited as powerful inhibitors of the hemorrhagic and clotting activity, possibly due to interaction with metalloproteases and thrombin-like enzymes. 25 Studies of several plants ( Heliconia curtispatha , Pleopeltis percussa , Brownea rosademonte , Bixa orellana (紅木 hóng mù), Trichomanes elegans , Struthanthus orbiculareis and Casearia sylvestris (林生腳骨脆 lín shēng jiǎo gǔ cuì) describe the inhibitory effect of all or part of the coagulant activity of snake venoms from B. asper , B. jararacussu , B. pirajai , B. neuwiedi , B. moojeni and C. d. terrificus . 26 , 27 , 28 The present study documents 38 species of ethnomedicinal plants from 25 families used by the tribal healers and medical practitioners in non-tribal communities.…”
Section: Discussionmentioning
confidence: 99%
“…Further investigations reveal that extracts from plants and their antioxidant components can neutralize the myotoxic effects induced by certain toxins such as BthTx-II [51,52]. This enzyme is known to causes evident muscle tissue damage characterized by distinct ultra-structural modifications, which can be measured through the CK levels.…”
Section: Discussionmentioning
confidence: 99%